Adriana Boscaro, Ed. y Trad. 101 Letters of Hideyoshi, the private correspondence of Toyotomi Hideyoshi. Tokyo, Sophia University, 1975. 113 pp. (Monumenta Nipponica, Monograph, 54.) - M. O. M. (El Colegio de México, A.C., 1975)
-